Azole Antifungal Resistance in Candida albicans and Emerging Non-albicans Candida Species - Whaley, Sarah G.; Berkow, Elizabeth L.; Rybak, Jeffrey M.; Nishimoto, Andrew T.; Barker, Katherine S.; Rogers, P. David (Frontiers in Microbiology, 2017)
Within the limited antifungal armamentarium, the azole antifungals are the most frequent class used to treat Candida infections. Azole antifungals such as fluconazole are often preferred treatment for many Candida infections as they are inexpensive, exhibit limited toxicity, and are available for oral administration. There is, however, extensive documentation of intrinsic and developed resistance to azole antifungals among several Candida species. As the frequency of azole resistant Candida isolates in the clinical setting increases, it is essential to elucidate the mechanisms of such resistance in order to both preserve and improve upon the azole class of antifungals for the treatment of Candida infections. This review examines azole resistance in infections caused by C. albicans as well as the emerging non-albicans Candida species C. parapsilosis, C. tropicalis, C. krusei, and C. glabrata and, in particular, describes the current understanding of molecular basis of azole resistance in these fungal species.